Pergumulan Praktik, Identitas dan Otoritas Islam di Indonesia Timur - Wahid, Abdul (Studia Islamika, 2020)
Kathryn M. Robinson (Ed.). 2020. Mosques and Imams: Everyday Islam in Eastern Indonesia. Singapore: NUS Press, National University of Singapore.This book provides an in-depth and critical narrative that contributes to a better understanding of Indonesian Muslim society's complexities and shifts. In contrast to studies on the dynamics of Islam in the western part of Indonesia, especially Java, which is centered on the figures of kiyai and Islamic boarding schools (pesantren) or Islamic schools (madrasah) institutions, the subjects of this study are mosques and imams. Both of which play a role as locus and agents of Islamization in Eastern Indonesia. With an ethnographic approach, this book is highly rich in details and insights that describe the particularity, diversity, nuances, as well as dimensions of Muslim communities in South Sulawesi, Maluku, East Nusa Tenggara, and West Nusa Tenggara. This book argues that religious authorities (imams) are autonomous figures who have considerable capacity to act, which enables them to shape their people's specific experiences and identities by utilizing mosques as sites to exercise their agency.